Complications Associated with Teenage Pregnancy in Nongkhai Hospital - Tuttinapanich, Piriya (Health Science Clinical Research, 2020)
Object: To compare complication of teenage pregnancy with adult pregnancy in Nongkhai Hospital. Method: This study was a retrospective analytic cohort study. The data were collected from medical records and the birth registration forms, from 1st January 2019 to 31st December 2019 then divided mother into 2 groups. The study group was comprised of 281 teenage pregnancy which less than 20 years, while the control group comprised of 1,714 adult pregnancy which age 20-34 years who were delivered in Nongkhai Hospital. Data were presented as frequency, percentage, mean, standard deviation and were analyzed by Independent t-test, Chi square test, Fisher’s exact test and Odd Ratio with 95% confidence interval. A p-value less than 0.05 was statistically significant. Results: The study found that teenage pregnancy had significantly higher rate of anemia (OR 1.440; 95%CI 1.107-1.874; p=0.006), neonatal low birth weight (OR 2.132; 95%CI 1.507-3.015; p<0.001), APGAR score less than 7 at 1 minute (OR 1.798; 95%CI 1.141-2.833; p=0.015) and meconium stain fluid (OR 1.263; 95%CI 1.844-1.874; p=0.016). Others; gestational diabetes mellitus, placenta previa, abruptio placenta, preterm delivery, intrauterine growth restriction, pregnancy induced hypertension,premature rupture of membrane, postpartum hemorrhage, and APGAR score less than 7 at 5 minutes were not significant different between the two groups. Conclusion: Teenage pregnancy have more chance to get maternal and neonatal complications more than adult pregnancy. They should receive proper antenatal care and effective contraception. Keywords: Teenage pregnancy, Complication of pregnancy.